A Phase II, Single-Arm Study of Apatinib and Oral Etoposide in Heavily Pre-Treated Metastatic Breast Cancer - Hu, Nanlin; Zhu, Anjie; Si, Yiran; Yue, Jian; Wang, Xue; Wang, Jiayu; Ma, Fei; Xu, Binghe; Yuan, Peng (Frontiers in Oncology, 2021)
Introduction We performed this clinical trial to evaluate the efficacy and safety of apatinib and oral etoposide in patients with HER2-negative locally advanced or metastatic breast cancer (MBC). Methods Patients with HER2-negative MBC previously treated with anthracycline and taxanes and failed ≥1 prior chemotherapy regimens were recruited. The starting dose of apatinib was 500 and 425 mg in patients with ECOG scores of 0–1 and 2, respectively. The etoposide capsules were given at 50 mg/m2 on days 1 to 10 for 21 days. The primary end point was objective response rate (ORR). Secondary end points included progression-free survival (PFS), disease control rate (DCR), overall survival (OS), and safety. Results Thirty-one eligible patients were enrolled. The median follow-up time was 11 months. The median PFS for all patients was 6.9 months [95% confidence interval (CI) 6.0–7.9], and 6.9 months (95% CI 5.3–8.6) and 6.6 months (95% CI 1.4–11.7) for patients with apatinib 425 and 500mg once daily, respectively. The ORR was 35.5% (11/31). The DCR was 87.1% (27/31). The median OS was 20.4 months (95% CI 11.4–29.3). The median PFS of patients who had hypertension and proteinuria was longer than that for those without hypertension and proteinuria. The most common grade 3/4 treatment-related AEs were hypertension (12/31, 38.7%), fatigue (3/31, 9.7%), thrombocytopenia (3/31, 9.7%). Conclusion Apatinib combined with etoposide capsules is effective and tolerable in heavily pretreated, metastatic HER2-negative breast cancer patients. A lower apatinib dose provide equivalent efficacy and reduced toxicity. Clinical Trial Registration https://clinicaltrials.gov/, identifier NCT03535961.